The synoptic skill of aerosol optical depth and angstrom exponent levels over the Mediterranean Basin. (25th November 2020) - Bodenheimer, Shalev; Nirel, Ronit; Lensky, Itamar M.; Dayan, Uri
Abstract: North African desert dust is the dominant aerosol type transported over the Mediterranean Basin (MB), followed by marine, anthropogenic, and biomass‐burning aerosol types. This basin is characterized by intense synoptic scale activity that has a substantial impact on the distribution of aerosols. A climatological research at a spatial resolution of 1° × 1° over the MB for the years 2000–2016 is presented here. We used a circulation to environment approach to examine the linkage between three objective circulation type classifications (CTCs) and two outcomes: aerosol optical depth (AOD) and Angstrom exponent (AE). This linkage, hereafter referred to as the 'synoptic skill', was assessed using tailored autoregressive linear regression and logistic models. We calculated (a) the total synoptic skill, accounting for the contribution of synoptic circulation type and the autoregressive components to AOD variability, and (b) the net synoptic skill, reflecting the contribution of the circulation type only. This novel approach enabled to differentiate between AOD distribution as controlled by the prevailing synoptic conditions to the one affected by climatic diurnal processes. Results for AOD showed maximal total synoptic skill during fall and summer ( R 2  ∼ 0.3) with highest values over parts of North Africa and the Middle East ( R 2  > 0.4). The net synoptic skill was highest ( R 2  ∼ 0.1) during winter and lowest ( R 2  ∼ 0.05) during summer. Geographic distribution showed low net values over North Africa and the Middle East ( R 2  < 0.06) and higher values over the Mediterranean Sea ( R 2  ∼ 0.1). For AE, the synoptic skill had a significant signature over Southern Europe during winter months ( c ‐statistic > 0.8). No single classification was superior in terms of mean synoptic skill, although for specific seasons and geographical locations one or the other of the three classifications showed higher performance. This study reflects some more evidences on the net contribution of CTCs to the distribution of AOD and AE over the MB. Abstract : We examined the synoptic skill of aerosol optical depth (AOD) and Angstrom Exponent using three objective synoptic classifications over the Mediterranean Basin. No single classification was superior, although for specific seasons and geographical locations one or the other of the three classifications showed higher performance. Higher AOD synoptic type skill is observed mainly for winter. Specific synoptic types with strong AOD anomaly distribution were characterized according to their synoptic‐scale circulation mechanisms, aerosol type, and seasonal distribution.